Inflation persistence on Services and Regulated Goods in Costa Rica - León Murillo, Jorge (2014)
The present document studies the degree of inflation persistence and price stickiness across different categories in the Costa Rican Consumer Price index (CPI), using disaggregate and aggregate data, with a particular focus in the regulated and services prices. We adopt two approaches: The parametric approach is based in an autoregressive process with constant mean, and the structural approach is based on the estimation of the New Keynesian Hybrid Phillips Curve. We use different econometric techniques, as univariate and multivariate time series, and panel data methods. The evidence suggests that changes in prices and services regulated items have higher degrees of persistence in addition to presenting rigidities in the adjustment pattern. Also it was found that using disaggregate data the degree of inflation persistence is lower than the inflation persistence estimation of univariate models with aggregate data, and this tend to reduce excluding the regulated and services products prices.